2021
DOI: 10.3892/ol.2021.13033
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA UCA1 enhances cervical cancer cell proliferation and invasion by regulating microRNA‑299‑3p expression

Abstract: The long non-coding RNA, urothelial cancer-associated 1 (UCA1) is an important regulator in several tumors. However, to the best of our knowledge, the clinical roles of UCA1 in cervical cancer remain unclear. Thus, the present study aimed to investigate the function and mechanism of UCA1 in cervical cancer. Reverse transcription-quantitative PCR analysis was performed to detect UCA1 and microRNA (miR)-299-3p expression in cervical cancer tissues and cell lines. The Cell Counting Kit-8 and Transwell assays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…According to the published articles, increasing evidence has demonstrated the underlying mechanisms and functions of lncRNAs at multiple regulatory levels 42 . Many existing articles indicated that UCA1 acts as a microRNA (miRNA) sponge 43–46 . Under this mechanism, UCA1 functions as an endogenous mimic target of miRNAs, resulting in the regulation of mRNA which is affected by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the published articles, increasing evidence has demonstrated the underlying mechanisms and functions of lncRNAs at multiple regulatory levels 42 . Many existing articles indicated that UCA1 acts as a microRNA (miRNA) sponge 43–46 . Under this mechanism, UCA1 functions as an endogenous mimic target of miRNAs, resulting in the regulation of mRNA which is affected by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…42 Many existing articles indicated that UCA1 acts as a microRNA (miRNA) sponge. [43][44][45][46] Under this mechanism, UCA1 functions as an endogenous mimic target of miRNAs, resulting in the regulation of mRNA which is affected by miRNAs. Nevertheless, numerous studies fall short of identifying the targeted miRNA or the location of UCA1, with substantial miRNA data retrieved from databases.…”
Section: Discussionmentioning
confidence: 99%
“…This was also accomplished in the SiHa cell line through the inhibition of miR-299-3p. The downregulation of miR-299-3p and subsequent tumor development caused by UCA1 overexpression were obvious in the CC tissues, as well [ 72 ].…”
Section: The Role Of Uca1 In CC Oncogenesis Proliferation and Invasionmentioning
confidence: 99%
“…They regulate proliferation, metastasis and invasion through different axis and through the suppression of specific miRNAs. UCA1 enhances cell proliferation and tissue invasion by upregulating KIF20A (Kinesin family member 20 A) expression via miR-204 sponging and via regulation of miR-299-3p expression [ 32 , 33 ]. Some recent studies have reported UCA1/miR-493-5p/HK2 (Hexokinase 2) axis interplay in the modulation of glycolytic pathway.…”
Section: Lncrnas As Clinical Utility Targetsmentioning
confidence: 99%
“…4. tissue invasion by upregulating KIF20A (Kinesin family member 20 A) expression via miR-204 sponging and via regulation of miR-299-3p expression [32,33]. Some recent studies have reported UCA1/miR-493-5p/HK2 (Hexokinase 2) axis interplay in the modulation of glycolytic pathway.…”
Section: Malat1 Was Observedmentioning
confidence: 99%